Measurement of calcitonin and cea in the needle washout fluid from thyroid nodule for the diagnosis of medullary thyroid carcinoma - N. V. Severskaya; I. V. Chebotareva; N. V. Zhelonkina; A. S. Belyakova; P. A. Isaev; V. V. Polkin; A. A. Ilyin; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал)
Background. medullary thyroid carcinoma (mtc) produces serum markers including calcitonin (ct) and carcinoembryonic antigen (cea). The measurement of ct in fine-needle aspirate washout fluid (FNA-CT) improves the cytological diagnosis of mtc. However, no data are available about cut-off values for FNA-CT using currently immunoassay. The measurement of cea in the needle washout fluid (FNa-cea) in mtc has not been studied.Objective: to assess the diagnostic value and propose cut-off values for FNA-CT and FNacea in the thyroid nodule to diagnose mtc.Material and Methods. We conducted a retrospective analysis of 164 samples of fine-needle aspirate washout fluid collected from 92 patients with thyroid nodules, who underwent FNa followed by cytological examination and measurement of FNA-CT. seventeen cases with mtc and 41 with non-mtc nodules were histologically verified. one hundred and six nodules identified as non-mtc by cytology were not operated on. FNa-cea was additionally studied in 29 samples. The cut-off value was determined by Roc analysis.Results. The FNA-CT level was >2000 pg/ml in all mtc nodules, except for one, in which the FNA-CT level was 638 pg/ml. In non-mtc nodules, the FNA-CT levels were <10 pg/ml and <100 pg/ml in 81 % and 90 %, respectively, however, it was >500 pg/ml in 5 %, and >1000 pg/ml in 2 %. At a cut-off value of 590 pg/ml, the sensitivity and specificity of FNA-CT were 100 % and 96 %, and at a cut-off of 1721 pg/ml, the corresponding values were 94 % and 99 %. The false positive FNA-CT values were 3.7 % and 1.2 % at the cut-off values of 590 pg/ml and 1721 pg/ml, respectively. The median levels of FNa-cea in mtc and non-mtc nodules were 59.3 ng/ml and 1.5 ng/ml, respectively. At a cut-off value of 7.5 ng/ml, the sensitivity of FNa-cea was 86 % and specificity was 100 %. Additional measurement of FNa-cea prevented all false-positive results of FNA-CT, but did not detect 2 mtcs with low FNa-cea levels (false-negative rate of 6.9 %). Among samples with FNA-CT value of >590 pg/ml and negative cytology (n=9), FNa-cea differentiated mtc with 100 % sensitivity and specificity.Conclusion. The maximum sensitivity of FNA-CT in the thyroid nodule was at a cut-off value of 590 pg/ml (100 %), the maximum specificity was at a cut-off value of 1721 pg/ml (99 %). Risk of false positive result is the major challenge of FNA-CT. to reduce false-positive results, we recommend to measure FNa-cea in the nodules with negative cytology and high level of FNA-CT. At a cut-off value of 7.5 ng/ml, FNa-cea allows the false-positive FNA-CT to be excluded.